Posttransplant de novo donor specific HLA antibody monitoring and clinical outcomes: a single-center experience - Ay, Nurettin; Alp, Vahhac; Kaya, Şeyhmus (The European Research Journal, 2021)
Objectives: Despite the improvements in early-term outcomes of kidney transplantation, late-term graft failure still remained as a critical problem. De novo donor specific antibodies (DSA) developing against direct human leukocyte antigens (HLA) are the significant risk factors for shortened graft survival in the previously non-sensitized cases. The purpose of this study is to evaluate the clinical outcomes of de novo DSA development in the kidney transplant cases. Methods: The present study included 121 (alive/cadaver: 106/15) of 148 (alive/cadaver: 125/23) cases who were not previously sensitized (PRA and DSA negative) and undergone kidney transplantation between August 2012-January 2018. DSAs of the cases without expected declines in creatinine levels in the polyclinic follow-ups and postoperative early-term were evaluated. Renal biopsy was performed in the cases encountered with >2000 mean fluorescence intensity (MFI) de novo DSA against HLA-A, HLA-B, HLA-DR. Treatment protocol of plasmapheresis+intravenous immunoglobulin (IVIG)+rituximab (in the cases without clinical response) was administered in the cases with antibody-mediated rejection (AMR) detected by renal biopsy. In addition, the presence of de novo non-DSA was also evaluated in the cases. The presence of de novo was encountered by identifying the specificities of anti-HLA antibody specificities using Luminex single antigen beads in the recipient serum. Results: De novo DSA (antibodies against HLA-A, HLA-B, HLA-DR and HLA-DQ) were monitored in 23 cases. DQ positivity was detected in 10 cases. MFI values were > 4000 and 2000-4000 in 8 and 2 cases, respectively. De novo non-DSA was found in 19 cases. Biopsy was performed in 8 cases due to the development of MFI > 2000 de novo DSA against HLA-A, HLA-B and HLA-DR and the findings of acute humoral rejection (AHR) were encountered in 2 cases. Additionally, acute humoral rejection was diagnosed in 1 case that developed de novo non-DSA. Two cases were diagnosed with AHR by biopsy although no de novo DSA or non-DSA developed and renal graft loss occurred in these two cases. Conclusions: The fact that routine DSA monitoring in all the cases provided no significant contribution to the outcomes of our study may contribute to the debates on the necessity of DSA monitoring in the patients with low immunological risk.